Determinan Persalinan Sectio Caesarea Pada Ibu Bersalin Di Rumah Sakit X Pekanbaru Tahun 2019 - nurhelmi helmi; Zulmeriza Rasyid (STIKes Hang Tuah Pekanbaru, 2020)
Sectio Caesarea Is A Surgery To Give Birth To The Fetus Via The Incision On The Abdomen And Uterus. Based On Early Observation Conducted Researchers Obtained The Normal Maternity Was 106 (20,7%) And 406 (79,3%) With Sectio Caesarea At January- March 2019. This Purpose Of This Study To Know The Determinant Of Sectio Caesarea At Maternity In X Hospital Pekanbaru. The Research Used A Method Of Analytic Survey With The Design Of Cross Sectional Study. The Total Of  Population 512 And Sample Of This Research 81 Maternities Who Were Birthing In The Hospital. Sampling Techniques Used Consecutive Sampling. The Measuring Instrument  Used A Questionnaire And Computerized Data Processed. Analysis Used Of Univariate And Bivariate With Chi-Square Test. Results Of The Studied In X Hospital Pekanbaru  There Was 51 (63%) Sectio Caesarea And 30 (37%) Normal Childbirth, After Analysis There Was Relationship Between Knowledge (P= 0,041, Or= 2,909 (1,142- 7,409)), Premature Of Membranes (P=0,041 Or=3,159 (1,152-8,662)), And Hypertension ((P=0,025, Or=3,348 (1,257-8,914)) With Sectio Caesarea. Expected For The Health Promotion And Health Of Both Mother And Child In X Hospital Pekanbaru To More Actively Educated About Maintaining Health During Pregnancy, Normal Childbirth And Sectio Caesarea Childbirth.